2018
DOI: 10.1002/cncr.31343
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of risk of infertility among male survivors of childhood cancer: A report from the Childhood Cancer Survivor Study

Abstract: Many male survivors of childhood cancer are unaware of how their cancer treatments could impact their reproductive health, underscoring the need for all patients to receive education regarding their risk of infertility throughout the continuum of cancer care. Cancer 2018;124:2447-55. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…This is, to our knowledge, the first study to systematically highlight the intersection of self-reported infertility risk perceptions and actual fertility status in a large cohort of childfree adult survivors of childhood cancer. Consistent with previous research, 19,36 most survivors perceived themselves at increased risk for infertility. Yet, although female survivors tend to be infertile at lower rates than male survivors, 7,55 both sexes had similar risk perceptions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is, to our knowledge, the first study to systematically highlight the intersection of self-reported infertility risk perceptions and actual fertility status in a large cohort of childfree adult survivors of childhood cancer. Consistent with previous research, 19,36 most survivors perceived themselves at increased risk for infertility. Yet, although female survivors tend to be infertile at lower rates than male survivors, 7,55 both sexes had similar risk perceptions.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies examined survivors' infertility risk perceptions in conjunction with gonadotoxic treatment exposure (as a proxy for increased infertility risk) and reported that risk perceptions did not differ by treatment exposure. 19,36 Although important, reliance on treatmentindicated risk in fertility counseling falls short, because different responses to therapy yield variability in survivors' fertility after treatment. Furthermore, previous studies did not assess whether survivors' fertility-related perceptions align with their actual gonadal functioning.…”
Section: Introductionmentioning
confidence: 99%
“…tested whether they also affect parenthood attitudes given that many childhood cancer survivors are unaware of infertility risks and their own gonadal functioning. [37][38][39]…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the importance of discussing fertility risk and available preservation options with patients newly diagnosed with NHL. While clinical practice guidelines have been developed to aid providers in identifying and counselling cancer survivors at risk for infertility (Kenney et al , ; Loren et al , ; Metzger et al , ), discordant perceptions and worry about risk have been described among both male and female childhood cancer survivors (Gilleland Marchak et al , , ), suggesting a need for ongoing patient education regarding fertility risks throughout the continuum of cancer and survivorship care.…”
Section: Fertilitymentioning
confidence: 99%